Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm tried to do following and I can't see what went wrong. $$\begin{bmatrix} \hat r\\ \hat \theta \end{bmatrix} = \begin{bmatrix} \cos \theta & \sin \theta \\ -\sin \theta & \cos \theta \end{bmatrix} \times \begin{bmatrix} \hat i\\ \hat j \end{bmatrix} $$ Taking inverse, $$ \begin{bmatrix} \hat i\\ \hat j \end{bmatrix} = \begin{bmatrix} \cos \theta & -\sin \theta \\ \sin \theta & \cos \theta \end{bmatrix} \times \begin{bmatrix} \hat r\\ \hat \theta \end{bmatrix} $$ The gradient of function $ \phi $ $$\nabla \phi = \hat i \frac{\partial \phi}{\partial x} + \hat j \frac{\partial \phi}{\partial y}$$ $$= \hat r \left( \cos \theta \frac{\partial \phi}{\partial x} + \sin \theta \frac{\partial \phi}{\partial y} \right) + \hat \theta \left( -\sin \theta \frac{\partial \phi}{\partial x} + \cos \theta \frac{\partial \phi}{\partial y} \right)$$ $$= \hat r \left( \cos \theta \frac{\partial \phi}{\partial r} \frac{\partial r}{\partial x} + \sin \theta \frac{\partial \phi}{\partial r} \frac{\partial r}{\partial y} \right) + \hat \theta \left( -\sin \theta \frac{\partial \phi}{\partial \theta} \frac{\partial \theta}{\partial x} + \cos \theta \frac{\partial \phi}{\partial \theta}\frac{\partial \theta}{\partial y} \right)$$ $$= \hat r \left( \cos \theta \frac{\partial \phi}{\partial r} \frac{1}{\cos \theta} + \sin \theta \frac{\partial \phi}{\partial r} \frac{1}{\sin \theta} \right) + \hat \theta \left( -\sin \theta \frac{\partial \phi}{\partial \theta} \frac{1}{- r \sin \theta } + \cos \theta \frac{\partial \phi}{\partial \theta}\frac{1}{ r\cos \theta } \right)$$ $$ = 2 \left ( \frac{\partial \phi }{\partial r}\hat r + \frac{1}{r} \frac{\partial \phi}{\partial \theta } \hat \theta\right )$$ I don't know what went wrong. Please help. Thank you!!

share|improve this question
    
You wrote: $$\frac{\partial \phi}{\partial x} = \frac{\partial \phi}{\partial r} \frac{\partial r}{\partial x}$$ instead of: $$\frac{\partial \phi}{\partial x} = \frac{\partial \phi}{\partial r} \frac{\partial r}{\partial x} + \frac{\partial \phi}{\partial \theta} \frac{\partial \theta}{\partial x}$$ –  qoqosz Jun 26 '12 at 16:39
    
@qoqosz please if you can help me to improve my knowledge –  Santosh Linkha Jun 26 '12 at 16:43

1 Answer 1

up vote 2 down vote accepted

You have incorrect expressions for $\dfrac{\partial r}{\partial x}, \dfrac{\partial r}{\partial y}, \dfrac{\partial \theta}{\partial x}$ and $\dfrac{\partial r}{\partial y}$. \begin{align} \dfrac{\partial r}{\partial x} & = \cos(\theta)\\ \dfrac{\partial r}{\partial y} & = \sin(\theta)\\ \dfrac{\partial \theta}{\partial x} & = -\dfrac1r \sin(\theta)\\ \dfrac{\partial \theta}{\partial y} & = \dfrac1r \cos(\theta) \end{align}

It is incorrect to think that $$\dfrac{\partial r}{\partial x} = \dfrac1{\dfrac{\partial x}{\partial r}}$$ $$\dfrac{\partial r}{\partial y} = \dfrac1{\dfrac{\partial y}{\partial r}}$$ $$\dfrac{\partial \theta}{\partial x} = \dfrac1{\dfrac{\partial x}{\partial \theta}}$$ $$\dfrac{\partial \theta}{\partial y} = \dfrac1{\dfrac{\partial y}{\partial \theta}}$$ which is what you seem to have done.

When you take partial derivatives, what you are doing is to hold the other variable fixed. So for instance if $f$ is a function of $n$ variables, $f(x_1,x_2,\ldots,x_n)$, $\dfrac{\partial f}{\partial x_i}$ means you hold all the other $x_j$'s constant except $x_i$ and vary $x_i$ by $\delta x_i$ and find out what happens to $\delta f$.

We have

$$x= r \cos(\theta) , y= r \sin(\theta), r^2= x^2 + y^2 \text{ and }\tan(\theta) = \frac{y}{x}$$

We are transforming from the $(x,y)$ space to $(r,\theta)$ space.

In the $(x,y)$ space, $x$ and $y$ are independent variables and in the $(r,\theta)$ space, $r$ and $\theta$ are independent variables.

$\dfrac{\partial x}{\partial r}$ means you are fixing $\theta$ and finding out how changing $r$ affects $x$.

So $\dfrac{\partial x}{\partial r} = \cos(\theta)$ since $\theta$ is fixed.

$\dfrac{\partial r}{\partial x}$ means you are fixing $y$ and finding out how changing $x$ affects $r$.

So $\dfrac{\partial r}{\partial x} = \dfrac{x}{\sqrt{x^2+y^2}}$ since $y$ is fixed.

When you do $r = \dfrac{x}{\cos(\theta)}$ and argue that $\dfrac{\partial r}{\partial x} = \dfrac{1}{\cos (\theta)}$ you are not holding $y$ constant.

If you were to hold $y$ constant, then $\theta$ would change as well.

If you want to use $r = \dfrac{x}{\cos(\theta)}$ and would like to get the right answer, you need to do as follows:

$r = \dfrac{x}{\cos(\theta)}$, $\delta r = \dfrac{\delta x}{\cos(\theta)} + \dfrac{-x}{\cos^2(\theta)} (-\sin(\theta)) \delta \theta$.

$\tan(\theta) = \dfrac{y}{x} \Rightarrow x \tan(\theta) = y$

$\delta x \tan(\theta) + x \sec^2(\theta) \delta \theta = 0$ (Since $y$ is held constant)

$x \delta \theta = - \dfrac{\delta x \tan(\theta)}{\sec^2{\theta}} = - \sin(\theta) \cos(\theta) \delta x$.

Plugging the above in the previous expression, we get

$\delta r = \dfrac{\delta x}{\cos(\theta)} + \dfrac{\sin(\theta)}{\cos^2(\theta)} (-\sin(\theta) \cos(\theta) \delta x) = \dfrac{1-\sin^2(\theta)}{\cos(\theta)} \delta x = \cos(\theta) \delta x$ and hence we get

$\dfrac{\partial r}{\partial x} = \cos(\theta) = \dfrac{x}{\sqrt{x^2+y^2}}$

share|improve this answer
    
how?? isn't $x = r \cos \theta$, $ \frac{\partial r}{\partial x} = \frac{1}{\frac{\partial x}{\partial r}} = \frac{1}{\cos \theta} $ ?? –  Santosh Linkha Jun 26 '12 at 16:34
    
thanks i understand .. :) –  Santosh Linkha Jun 26 '12 at 16:41

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.